2008
DOI: 10.5334/pb-48-1-37
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for a Food-Related Attention Bias after Thought Suppression

Abstract: The aim of this study was to investigate whether food-related thought suppression results in an attention bias for food cues. Fifty-nine female students took part in the experiment. All completed a modified exogenous cueing task containing pictures of foods and toys with a similar valence (presentation duration: 250 ms and 1050 ms). Half of the participants were instructed to suppress thoughts about food and the other half was given control instructions, prior to completing the exogenous cueing task. No eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
3
1
Order By: Relevance
“…These results are not in line with some previous research, in which all participants generally displayed an AB for food, thus all participants paid more attention to food than to neutral stimuli (e.g., Werthmann, Jansen, & Roefs, 2016;Werthmann et al, 2013). However, also some other studies did not detect an AB for food in participants in general (Liu, Roefs, & Nederkoorn, 2021;Pimpini, Kochs, van Zoest, Jansen, & Roefs, 2022;Soetens, Braet, & Bosmans, 2008). This suggests that AB for food might not be always present.…”
Section: Ab For Foodcontrasting
confidence: 99%
“…These results are not in line with some previous research, in which all participants generally displayed an AB for food, thus all participants paid more attention to food than to neutral stimuli (e.g., Werthmann, Jansen, & Roefs, 2016;Werthmann et al, 2013). However, also some other studies did not detect an AB for food in participants in general (Liu, Roefs, & Nederkoorn, 2021;Pimpini, Kochs, van Zoest, Jansen, & Roefs, 2022;Soetens, Braet, & Bosmans, 2008). This suggests that AB for food might not be always present.…”
Section: Ab For Foodcontrasting
confidence: 99%
“…The nascent research investigating the relationship between thought suppression and eating behaviors have reported mixed findings. Some studies [3,4,5,6,7] found that the outcomes of thought suppression, such as hyperaccessibility and rebound, do result from attempting to suppress food-related thoughts, whereas one study did not [8,9,10]. The latter study, however, [8] did not examine if the outcomes of thought suppression differed between participants who were currently dieting versus not or healthy weight versus overweight/obese, both of which appear to affect the outcomes of thought suppression [11–13].…”
mentioning
confidence: 99%
“…Other studies have similarly reported lack of evidence for AB for food. For example, in a Posner cueing task, no AB for food was found ( Soetens, Braet, & Bosmans, 2008 ). Also, when investigating AB for food in overweight vs. lean individuals with a modified additional singleton task, no AB for food was observed on eye-tracking measures ( Pimpini, Kochs, van Zoest, Jansen, & Roefs, 2022 ).…”
Section: Discussionmentioning
confidence: 99%